The Potensi Mixed Reality Dalam Pembelajaran Praktikum Online - Adrian Permana Zen; Syarip Hidayat (Jurnal Sosioteknologi, 2022)
The world is facing new challenges in the digital era, especially when presented with the metaverse and other online platforms. The sector that is affected by this challenge is the education sector. Academics are faced with the challenge to keep up with digital developments toward society 5.0. The challenge is in the form of online learning. The use of software in online learning still benefits learning that is theoretical but ineffective in practicum learning due to unsupported technology. With the emergence of Augmented Reality and Virtual Reality technology, it is possible to make online learning by combining AR and VR technology, namely Mix Reality. Mix Reality provides enormous potential for online learning because it provides features that cannot be done with conventional online learning in general. The combination of Haptic AR, Audio AR, and gustatory and olfactory AR make online learning possible. Its application in online practicum, MR technology, has a crucial role because teachers can use MR to produce digital content with no restrictions and interact online with their students. Either through virtual spaces or a collaborative learning environment. This article discusses details about the potential of Mixed Reality for online practicum learning.